TINGKAT KETERBACAAN WACANA PADA BUKU PAKET KURIKULUM 2013 KELAS 4 SEKOLAH DASAR MENGGUNAKAN FORMULA GRAFIK FRY - Anih, Euis; Nurhasanah, Nesa (STKIP Subang, 2016)
Readability are all elements that exist in the text (including the interaction between text) that affect the success of the reader in understanding the material they read on the speed reading is optimal. Measure the readability of a discourse needs to be done by educators to the material presented on target. There are many ways to measure the readability level of discourse, one formula Fry Graph. Fry Graph formula is quite popular because the procedure is easy. Curriculum 2013, the government issued textbooks thematic. This study aims to determine the readability level of discourse using the formula Fru Graph in this thematic books, especially books Elementary School 4th grade thematic themes ?Indahnya Kebersamaan? and ?Selalu Menghemat Energi?. This study is a descriptive analysis method, namely: based on readability formulas introduced by Edward Fry, who became known as